O2-S4.06 Exploring enema practices among men who have sex with men in the USA: implications for sexual health. (10th July 2011) - Rosenberger, J G.; Herbenick, D; Van Der Pol, B; Novak, D S; Reece, M; Fortenberry, J D
Abstract : Purpose: Recent literature has suggested that use of hygiene products (ie, douching) by women and men prior to sexual activity, changes the biological makeup of vaginal and anal tissue, potentially affecting risk for HIV/STI acquisition. While men who have sex with men (MSM) continue to be disproportionately impacted by HIV/STI, little information exists about men's lifetime enema behaviours, the situational contexts impacting their use, and attitudes towards use of such products. Methods: Data were collected via an internet survey from 27 690 18–80 year old MSM. Measures included sociodemographics, recent/lifetime sexual behaviour history, and items related to enema use. Results: Participants' median age was 39.0 years; ethnicities included white (84.5%), Latino (6.4%), African American (3.5%); and, most (79.9%) identified as homosexual. Over half (54.2%) of men indicated that they were not currently in a romantic relationship and the majority (88.9%) reported having two or more sexual partners in the past year. Most men (64.5%) reported lifetime enema use, with 33.8% reporting use in the past month. Most common reasons for starting enema use were to avoid feces during sex (72.5%) and to feel clean during sex (65.6%). Among enema users, 34.4% reported use of a disposable store bought enema, while 62.5% indicated having used a refillable enema or one that attached to the shower. Men somewhat or strongly agreed that enema use increased comfort with their anus (75.8%), made sex more enjoyable (75.5%), and increased the likelihood of being the receptive partner (75.8%). During the most recent sexual event, enema use was reported both before (37.1%) and after (8.1%) sex, with most (42.0%) reporting use 30 min–1 h prior to sex. Enema use at last sex was more likely to occur among men who were Caucasian (p <0.01), who engaged in anal intercourse (p <0.01), and whose sexual partner was someone they just met (p <0.05). Conclusions: These data provide one of the first examinations of enema practices among MSM in the US. Findings highlight use of enemas prior to sexual activity as a common behaviour, and one associated with positively enhancing the sexual experience. The acceptability of enema use in this population may provide a vehicle for microbicide or virocide delivery once such compounds are fully developed. Future research should examine the relationship between behavioural practices and biological impacts of enema use in relation to HIV/STI.